Nickel‐Based Transition Metal Nitride Electrocatalysts for the Oxygen Evolution Reaction - Tareen, Ayesha Khan; Priyanga, G. Sudha; Khan, Karim; Pervaiz, Erum; Thomas, Tiju; Yang, Minghui (ChemSusChem, 2019)
Electrocatalysis is an efficient and promising means of energy conversion, with minimal environmental footprint. To enhance reaction rates, catalysts are required to minimize overpotential. Alternatives to noble metal electrocatalysts are essential to address these needs on a large scale. In this context, transition metal nitride (TMN) nanoparticles have attracted much attention owing to their high catalytic activity, distinctive electronic structures, and enhanced surface morphologies. Nickel‐based materials are an ideal choice for electrocatalysts given nickel's abundance and low cost in comparison to noble metals. In this Minireview, advancements made specifically in Ni‐based binary and ternary TMNs as electrocatalysts for the oxygen evolution reaction (OER) are critically evaluated. When used as OER electrocatalysts, Ni‐based nanomaterials with 3 D architectures on a suitable support (e.g., a foam support) speed up electron transfer as a result of well‐oriented crystal structures and also assist intermediate diffusion, during reaction, of evolved gases. 2 D Ni‐based nitride sheet materials synthesized without supports usually perform better than 3 D supported electrocatalysts. The focus of this Minireview is a systematic description of OER activity for state‐of‐the‐art Ni‐based nitrides as nanostructured electrocatalysts. A revolution in evolution: The electrocatalytic oxygen evolution reaction is a promising means of efficient energy conversion, with minimal environmental footprint. Transition metal nitride nanoparticles have attracted much attention owing to their high electrocatalytic activities, distinctive electronic structures, and enhanced surface morphologies. Nickel‐based electrocatalysts are of particular interest, given their abundance and low cost.